Remembering the role of the Reformed Churches in the struggle for justice in South Africa (1960-1990): some remarks on the promise and pitfalls of memory and historiography - Vosloo, Robert R (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The period 1960-1990 represents a dramatic – and also traumatic – period in South African church and theological history. The story of the Reformed churches during this period is inextricably interwoven with the theological support of the ideology of apartheid as well as the story of the theological struggle against the injustices of apartheid. With this in mind this essay addresses the question: “How should we remember the role of the Reformed churches in South Africa in the struggle for justice between 1960 and 1990?” The essay attends to various aspects of this question, offering some clarification and qualification in the process. The article argues, in addition, that an engagement with the role of the Reformed churches in South Africa in the struggle for justice requires an awareness of the promise as well as the pitfalls associated with the attempt to remember and to represent the past.